Rancang Bangun Aplikasi Perencanaan Bahan Baku Makanan Menggunakan Metode MRP Pada Rumah Sakit Islam Jemursari Surabaya - Al Thariq, Mohammad Dzulfikar; Sudarmaningtyas, Pantjawati; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
Nutritional installation at Jemursari Surabaya Islamic Hospital is responsible for serving the nutritional needs of patients. Two problems faced in this process, namely inaccuracy in the procurement of planned food and raw materials and errors in the calculation of food raw materials. These problems cause damage to the raw materials because of excess stock or affect the production process because the raw materials are not available. The solution to the problem above with embedding Material Requirement Planning (MRP) method on the application so that it can automatically calculate raw material planning used the Lot-For-Lot technique. This application was developed using the SDLC method. It can be concluded that this study has produce application can run appropriately according to its function.Â  It is based on the test results to reach 96.87%.